Zapisz w postaci jak najprostszej sumy algebrqicznej. Na jutro!!!

A) 3a (2b + 4 ) + 2a (3- 5b) =
-2x (5x - y) - x ( 8x - 2y) =
5p (2 + 3r - p) - 3p (2p - 4) =
3k (4-5m + 2k) - 3m (2-3k) =


Odpowiedź :

1)

[tex]3a(2b+4)+2a(3-5b)=\\\\=6ab+12a+6a-10ab=\\\\=6ab-10ab+12a+6a=\boxed{-4ab+18a}[/tex]

2)

[tex]-2x(5x-y)-x(8x-2y)=\\\\=-10x^2+2xy-8x^2+2xy=\\\\=-10x^2-8x^2+2xy+2xy=\boxed{-18x^2+4xy}[/tex]

3)

[tex]5p(2+3r-p)-3p(2p-4)=\\\\=10p+15pr-5p^2-6p^2-12p=\\\\=-5p^2-6p^2+10p-12p+15pr=\boxed{-11p^2-2p+15r}[/tex]

4)

[tex]3k(4-5m+2k)-3m(2-3k)=\\\\=12k-15km+6k^2-6m+9km=\\\\=6k^2-15km+9km+12k-6m=\boxed{6k^2-6km+12k-6m}[/tex]